Evaluation of Functional and Radiological Outcome of Different Cephalomedullary Nail Designs in Intertrochanteric Fractures of Femur - Adarsh U Thuppad; Harsh Kirthi Rao; Gaurav C Mendon; Santosha Manjunatha; Suraj M Revankar; Kaveesh P Shetty (Journal of Orthopaedic Case Reports)
Introduction: The incidence of intertrochanteric (IT) fracture is rising because of increase in the survival of the elderly population with osteoporosis and also the increase in the number of motor vehicle accidents. The treatment of choice is normally surgical with internal fixation. The surgical options for these fractures commonly include fixation with dynamic hip screw (DHS) or cephalomedullary nailing. Due to its advantages over DHS, cephalomedullary nailing is the predominant procedure in many parts of the world. Various varieties of cephalomedullary nails are available. Short cephalomedullary nails are indicated for IT fractures not extending beyond lesser trochanter. There are limited studies on the comparison of short cephalomedullary nails for IT fracture. In this study, we are evaluating functional outcome, radiological union and complications of inter-trochanteric fractures of femur treated with three different short cephalomedullary nails: (1) Proximal femoral nail (PFN)-standard, (2) modified short PFN (MS-PFN) and (3) PFN-A2 of 240 mm. Materials and Methods: Our study is a randomized control trial. Subjects are patients with IT fracture presenting to Srinivas Institute of Medical Sciences and Research Centre. After obtaining informed and written consent, as per inclusion and exclusion criteria, subjects are randomized into three groups (simple randomization) and treated with standard PFN (240 mm length), MS-PFN (180 mm length), and PFN-A2 of length 240 mm as per randomisation. Duration of the surgery and total intraoperative blood loss is noted. Patients are followed up till 1-year post-operative period, in different intervals. Functional outcome using Harris hip score, fracture union, complications are assessed and compared. Considering the lost to follow-up, the final study size obtained is 75 (25 in each group). Results: In our study, the average age of the patients is 71.29 years with male predominance and right-side predominance. Majority of the fractures belong to Type 1 Group 2 and type 1 Group 4 of Evan’s classification. The average operating time and average intraoperative blood loss is less in PFN-A2 group compared to PFN and MS-PFN groups. The fracture union time is earlier in PFN A2 group compared to PFN and MS-PFN group. Functional outcome is better in PFN-A2 group compared to PFN and MS-PFN groups. In PFN group and PFN A2 of 240 mm length group, there were significant patients with anterior thigh pain. Among 75 patients, 3 in PFN group, 2 in MS-PFN group, and 1 in PFN-A2 group had >1 cm of shortening. 2 patients in PFN group and 1 in MS-PFN group had complication of screw cut-out; 2 in PFN group and 2 in PFN-A2 group had surgical site infection; 1 in PFN group and 1 in PFN-A2 group had varus collapse; and 1 in PFN group and 2 in MS-PFN group had Z effect/reverse Z effect. Conclusion: In our study, on comparing three short nails – PFN, MF-PFN, and PFN-A2, PFN-A2 is superior in terms of operating time, intraoperative blood loss, functional outcome and fracture union. MS-PFN is next to PFN-A2 in the above parameters. Hence, PFN-A2 is superior to MS-PFN and MS-PFN is superior to PFN. Moreover, to avoid anterior thigh pain, we recommend the use of shorter nails (180 mm).